Effect of Beta-Alanine Supplementation on 2,000-m Rowing-Ergometer Performance - Ducker, Kagan; Dawson, B.; Wallman, K. (Human Kinetics, 2013)
Ducker Kagan, Effect of Beta-Alanine Supplementation on 2,000-m Rowing-Ergometer Performance, 2013